2021
DOI: 10.1007/s40808-021-01158-9
|View full text |Cite
|
Sign up to set email alerts
|

The influence of awareness campaigns on the spread of an infectious disease: a qualitative analysis of a fractional epidemic model

Abstract: Mass-media coverage is one of the most widely used government strategies on influencing public opinion in times of crisis. Awareness campaigns are highly influential tools to expand healthy behavior practices among individuals during epidemics and pandemics. Mathematical modeling has become an important tool in analyzing the effects of media awareness on the spread of infectious diseases. In this paper, a fractional-order epidemic model incorporating media coverage is presented and analyzed. The problem is for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Spreading awareness was particularly identified as an efficient means, especially when conducted by influential people in the community such as religious and community leaders. These results are complemented by other researchers who found that public awareness is an efficient mean to limit the spread of infectious diseases ( Abdelhafiz et al, 2020 , Akdim et al, 2021 ). They suggest that the role of public awareness and that of influential people should not be overlooked in the context of a pandemic such as COVID-19 ( Wan et al, 2020 ).…”
Section: Discussionsupporting
confidence: 58%
“…Spreading awareness was particularly identified as an efficient means, especially when conducted by influential people in the community such as religious and community leaders. These results are complemented by other researchers who found that public awareness is an efficient mean to limit the spread of infectious diseases ( Abdelhafiz et al, 2020 , Akdim et al, 2021 ). They suggest that the role of public awareness and that of influential people should not be overlooked in the context of a pandemic such as COVID-19 ( Wan et al, 2020 ).…”
Section: Discussionsupporting
confidence: 58%
“…Several fractional operators have been devised to explore the dynamics of epidemic systems, including Caputo-Fabrizio, Riemann-Liouville, Caputo, Hadamard, Atangana-Baleanu, Katugampola, and others. We employed the Caputo operator to examine the dynamics of COVID-19, since it has a nonlocal and nonsingular exponential kernel [35][36][37][38][39][40]. The dynamical and nonstandard computational study of a heroin epidemic model is discussed by Raza et al [41].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, several fractional-order models have studied epidemic dynamics through a system of fractional ordinary differential equations [ 6 10 , 14 – 20 ]. Many works involving fractional calculus are mainly focused on SIR-type models (see for instance [ 6 , 14 , 15 , 19 ]). Saeedian et al [ 6 ] studied the effect of memory on the evolution of epidemics by means of fractional SIR epidemic model using the Caputo fractional operator.…”
Section: Introduction and Model Formulationmentioning
confidence: 99%
“…Recently, Djilali et al [ 20 ] presented and analyzed a fractional epidemic model with nonlinear incidence rate. Lately, Akdim et al [ 19 ] have mainly studied the role of awareness campaigns strategies on the spread of an infectious disease using a Caputo fractional epidemic model with nonlinear-incidence function.…”
Section: Introduction and Model Formulationmentioning
confidence: 99%